Success in Elements of Banking - Cox David (John Murray Publishers Ltd, 1983)
This book is for anyone who wants to follow a self-study course. The Business of Banking, The Development of Money, The Development of Banking in Britain, The Bank of England, The British Banking Structure, Savings and Investment, The London Money Market, A Bank's Balance Sheet, Organizational Structure of a London Clearing Bank, Bills of Exchange and Cheques, Methods of Payment Through the Banking System, Who are the Customers?, Bank Accounts, Banking Services: Personal Customers, Banking Services: Business Customers, Banking Services for the Exporter and Importer, Bank Lending, Interpreting the Accounts of Customers, The Institute of Bankers, Further Questions, Assignments, Further Reading, Answers to Questions, Index.